2018
DOI: 10.1007/s40263-018-0502-z
|View full text |Cite
|
Sign up to set email alerts
|

Use of α2δ Ligands for Restless Legs Syndrome/Willis Ekbom Disease

Abstract: Restless legs syndrome is a common neurological condition affecting a substantial portion of the population. It can be an idiopathic disorder, or one that is secondary to another cause. Given that the underlying pathophysiology of restless legs syndrome is not well understood, several drug classes have been studied for symptom control. While dopamine agonists have long been the mainstay of first-line treatment for restless legs syndrome, recently, the α2δ ligands have been increasingly used. These agents have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 97 publications
0
10
0
Order By: Relevance
“…Pregabalin binds to voltage-gated calcium channels, inhibits calcium entry, and results in lowering glutamate activity and therefore decreasing excitation ( 20 ). This mechanism is hypothesized to exert an effect on RLS treatment ( 12 ). Pregabalin has several additional beneficial aspects in the management of RLS that should also be considered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pregabalin binds to voltage-gated calcium channels, inhibits calcium entry, and results in lowering glutamate activity and therefore decreasing excitation ( 20 ). This mechanism is hypothesized to exert an effect on RLS treatment ( 12 ). Pregabalin has several additional beneficial aspects in the management of RLS that should also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, pregabalin is capable of controlling other comorbidities in RLS patients. As one of the alpha-2-delta ligands, it can be effective in controlling neuropathic pains and anxiety, for example ( 12 ). In addition, interaction with the BK channel has been suggested to reduce neuropathic pains ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies also conclude that the use of dopamine or α-2-δ calcium-channel ligand is recommended as the first-line treatment for RLS along with other agents depending on other factors including, the severity of RLS, cognitive function, and comorbid conditions [43]. In 2018, Faulkner reported that α-2-δ ligands were a better choice for RLS compared to dopamine agonists as α-2-δ ligands were both safer and more effective compared to dopamine agonists [44].…”
Section: Therapeutic Approaches To Rlsmentioning
confidence: 99%
“…As a result, gabapentinoids are useful drugs in the treatment of several neuropathies, such as neuropathic pain 2 and fibromyalgia 3 and other nonpain indications, such as epilepsy 4 or restless leg syndrome. 5 The overall function of the α2δ subunit is still a matter of intense research. 6 The mechanism of calcium current increase is unknown, and it can only be partially explained by an increase in the trafficking of the channels to augment their amount on the cell surface.…”
mentioning
confidence: 99%